PENGARUH PROFESIONALISME AUDITOR, TIME PRESSURE, ETIKA PROFESI DAN GENDER TERHADAP TINGKAT MATERIALITAS - Auditya Pratama; Rudi Ginting (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
The high competition between public accounting firms on an international scale and a national scale makes auditors forget their role and responsibility in carrying out inspection services based on International Auditing with high competition, making auditors commit financial statement fraud lately which began to be discussed and debated again, thus, this research is a quantitative study to test the influence of auditor professionalism, time pressure, professional ethics and gender on consideration of materiality levels over financial statements. The population in this study is an auditor registered with the Indonesian Institute of Public Accountants (IAPI) in the DKI Jakarta area, while for the research sample applying simple random sampling by distributing questionnaires to several auditors working in kap DKI Jakakarta area with a sample number of 81 auditors who filled out and returned questionnaires. Data analysis to test hypotheses applies multiple linear regressions with SPSS 21 software at a significance level of 0.05%. Data testing describes the professionalism of the auditor influences the consideration of the level of materiality over financial statements, then time pressure affects the consideration of materiality levels on financial statements, while professional ethics has no effect on consideration of materiality levels over financial statements, and gender affects the consideration of materiality levels on financial statements. Keywords: Professionalism, Time Pressure, Professional Ethics, Gender and Materiality